Secure communication in location based services (LBS) using advanced encryption standard 256(AES 256) / Nur Afiqah Mohd Noor - Mohd Noor, Nur Afiqah (2014)
Location based services are any services or software applications that requires the geographic location (longitude and latitude) of an entity. Nowadays, with the aid of smartphones, location based services have improved tremendously in the market with wide range of users. Many mobile applications implement location based services in their applications to gain the user's information for applications service purpose. Location based services are used in a variety of scopes such as health, indoor object search, entertainment, work and personal life. However, in many existing location based services, the user's information were not private where the service provider is aware with the user's location and may leak this information to any unauthorized entities. This may lead to misuse of information by the third party which could endanger the user. As an instance, thieves may use the geo-location to determine whether victim is at home or not, and they able to use the data to plan a burglary. Based on the issues, to encounter this problem a symmetric encryption can be used as a solution to encrypt the data sent within client and location based services. Symmetric encryption is used to protect user's information by convert the information to private text. Symmetric encryption performed the process of encryption and decryption by using same shared key between client and server. Symmetric encryption has some types such as Data Encryption Standard (DES) and Advanced Encryption Standard (AES). An experiment of symmetric encryption using TCP/IP client-server for protecting user's privacy in the communication had been conduct to prove the user's information is encrypted. Advanced Symmetric Encryption 256 (AES256) has been chosen among the symmetric encryption variations due to it benefits. This project demonstrates the process of creating the application which responsible for communication over TCP protocol between two computers and the user interface.